Pengendalian Jumlah Cacat Produk pada Proses Produksi Piring Plastik dengan Metode QCC (Quality Circle Control) di CV. Serba Jaya Oke - Sumiati, Sumiati; Firmansyah, Akbar Maulana (Universitas Batanghari Jambi, 2025)
CV. Serba Jaya Oke is a plastic-based household appliance company in Surabaya. This company is a pioneer in providing a variety of high-quality plastic products for household needs. In 2023, CV. Serba Jaya Oke experienced defects of 26% almost every month for its plastic plate production. The Quality Control Circle (QCC) method is an approach to handling defective plate products by involving employees in quality control. Identification in the QCC method also uses PDCA (Plan-Do-Check-Act), seven tools, and the 5W + 1H matrix to analyze the causes of defects and determine appropriate corrective actions. The results of improvements to the plastic plate production process for 1 month in May 2023 showed a decrease in defects from 25.7% to 6%.